Kepedulian Pemerintah Gampong Dan Peran Ekonomi Keluarga Terhadap Stunting Pada Anak Di Kecamatan Lueng Bata Banda Aceh - Dina Hanifa; Ismail; Irma Anggraini (STKIP Subang, 2026)
Stunting remains a serious health problem in Lueng Bata District, Banda Aceh, as it impacts children's physical growth, cognitive abilities, and social development. This condition is influenced by the village government's concern in implementing prevention programs, as well as the family's economic capacity to meet children's nutritional needs. This study aims to determine the village government's concern, the socioeconomic conditions of families, and the obstacles in addressing stunting in children in Lueng Bata District, Banda Aceh. This study used a descriptive qualitative approach with research subjects including two village government officials, four parents of stunted children, and two village health workers. Data collection techniques include observation, interviews, and documentation in Cot Mesjid Village and Blang Cut Village. Data analysis techniques through reduction, presentation, and drawing conclusions. The results indicate that the village government has made efforts through coordination with the Community Health Center (Puskesmas) and the Health Office, stunting discussions, as well as the provision of PMT (Food and Nutritional Supplements), milk, MBG (Based Nutrition Supplements), and support from Posyandu cadres. From an economic perspective, income, assets, housing facilities, and government assistance influence a family's ability to meet children's nutritional needs. However, stunting management remains hampered by socioeconomic limitations, suboptimal height/age monitoring, low parental attendance and commitment, and children's difficulty eating. This study concludes that stunting management requires synergy between village governments, families, and communities to be more effective and sustainable.